Analysis of the automated systems of planning of spatial constructions - Барабаш, М.С. (Proceedings of National Aviation University (archive), 2004)
The article is devoted to the questions of analysis of existing SAPR and questions of development of new information technologies of planning on the basis of integration of programmatic complexes with the use of united informatively-logical model of object.